Implementasi Kebijakan Penanganan dan Penanggulangan Kegiatan Penangkapan Ikan yang Merusak (Destructive Fishing) di Indonesia - Nasution, Anta Maulana; Rahman, Rizqi; Ramadhani, Cahaya (Badan Penelitian dan Pengembangan Provinsi Sumatera Utara, 2024)
Destructive fishing activities are a threat to the sustainability of fishery resources and harm fish stocks as well as environmental ecosystems. Comprehensive regulations are needed to cope with destructive fishing and ensure the regulations will be implemented well and appropriately. Using a qualitative approach, this study aims to scrutinize the implementation of policies issued by the central government in the regions, including laws and other national regulations related to coping with destructive fishing. North Maluku Province is the focus of the study to identify the implementation of national regulations in the region. In addition, this study also identifies the roles of maritime law enforcement agencies involved in efforts to supervise and implement national policies related to overcoming and preventing destructive fishing. The results reveal that existing laws are insufficient to cope with the destructive fishing criminal act. So far, eight actors have roles in the prevention and coping of destructive fishing activities, consisting of elements of maritime law enforcement agencies such as the Police, Indonesian Navy, Indonesian Coast Guard, and Directorate General of PSDKP, as well as civil or community elements such as the PWP3K Special Police, Forestry Police, Department of Marine Affairs and Fisheries, and Monitoring Community Supervisory Groups (Pokmaswas). Keywords: destructive fishing, Law, Maritime Law Agency, Gap